Caracterização e modelagem numérica do comportamento não linear do concreto de ultra-alto desempenho reforçado com fibras metálicas - França, Luis Henrique Pereira (2021)
This work had as main objectives the development and experimental characterization of the mechanical behavior of high-performance concretes. In this sense, ultra-high performance concrete mixes ( fck = 150 MPa) reinforced with metallic fibers were developed. Fiber contents ranged from 0%, 1% and 2%. To ensure good performance and high durability, the lines were produced by optimizing the particle size structure and using third-generation additives. Metakaolin, which is considered a secondary cementitious material, was also used. Metakaolin fills the gaps between the cement grains. The experimental program developed in this work aimed to obtain the fundamental constitutive properties for non-linear numerical analysis. Through experimental tests, properties such as static and dynamic modulus of elasticity, compressive strength, direct and indirect tensile strength, fracture energy, flexural modulus and the ductile tensile damage curve were obtained. Thus, the physical nonlinearity was obtained to validate the numerical modeling. After the end of the experimental program, numerical modeling via finite elements of the tests of direct traction and four-point bending in the software ABAQUS was carried out using the constitutive model Concrete Damaged Plasticity (CDP). Based on the results, it can be stated that the material has high resistance to compression and traction, high durability and high modulus of elasticity. It was noticed that the numerical models were able to satisfactorily represent the physical non-linearity of the material, in this sense, the constitutive model CDP can be used successfully in the representation of the behavior of high-performance concrete.